The Impact of Teacher Certification on Creativity in Islamic Primary Education - Asmi Fuadi Tanjung; Mahariah Mahariah (Universitas Negeri Semarang, 2025)
The study aimed to examine the influence of teacher certification on the creativity of Islamic religious education. Pendidikan Agama, Islam (PAI), teachers in the teaching and learning process at SDN 18, Bilah Barat. A quantitative ex post facto design with descriptive analysis was employed to investigate the relationship between certification and teacher creativity. The population comprised six grade students and one certified PAI teacher. From this population, a sample of 30 students was selected through cluster sampling. And the certified teacher was analyzed as the main subject. Data collection was conducted using validated instruments, including questionnaires, structured interviews and classroom observations to gather comprehensive insights into the variables under study. The hypothesis was tested using Chi Square analysis. The calculated chi square value (X2calculated = 20.074) exceeded the critical chi square value (X2table = 3.841) at significance level of 0.05 with one degree of freedom (df = 1) based on these results, the null hypothesis H0 was rejected, and the alternative hypothesis Ha was accepted. The findings indicated that teacher certification had a significant impact on the creativity of PAI teachers in classroom settings. The results provided empirical evidence supporting the theoretical assumption that certification improves teacher professionalism and creativity. Certification was shown to motivate teachers to design and implement innovative teaching strategies. Contributing to more dynamic and engaging educational practices, this study highlighted the critical role of teacher certification in fostering creativity, particularly in the context of PAI, where teaching involves shaping students moral and spiritual values alongside academic knowledge.